MRI-guided focused ultrasound ablation of painful lumbar facet joints: a retrospective assessment of safety and tolerability in human subjects - Tiegs-Heiden, Christin A; Hesley, Gina K; Long, Zaiyang; Lu, Aiming; Lamer, Tim J; Gorny, Krzysztof R; Hangiandreou, Nicholas J; Lehman, Vance T (Pain medicine (Malden, Mass.), 2023)
Abstract Objective To evaluate the safety and tolerability of MRI-guided focused ultrasound (MRgFUS) for the treatment of facet joint–mediated pain in human subjects for whom conventional treatment had failed. Secondarily, to evaluate effectiveness of the procedure. Methods Consecutive patients who underwent MRgFUS at our institution were retrospectively identified. Chart review was performed to obtain relevant clinical and technical data. All patients had chronic low back pain and positive comparative medial branch blocks. Results Twenty-six MRgFUS treatments in 20 patients were included. Mean sonication energy was 1436.6 Joules. The procedure was technically successful in all patients. Of the treated patients, 29.6% experienced short-term worsening of low back pain immediately after the procedure, all by 1–4 points on a 0–10 scale. One patient (3.8%) reported temporary worsening of preexisting radicular symptoms after the procedure. Of 21 treatments with clinical follow-up of at least 3 months available, 12 (57.1%) had >3 months’ pain relief, 2 (10%) had <3 months’ benefit, 6 (30%) reported no benefit, and 1 (5%) patient was lost to follow-up. In patients who reported at least some benefit with prior conventional radiofrequency ablation, 8/10 (80%) benefited from the MRgFUS procedure. Conclusion The present study demonstrates that MRgFUS ablation of the lumbar facet joints is a safe and tolerable procedure in human subjects and could provide another option for patients for whom radiofrequency ablation had failed. More than half of all patients received significant durable pain relief, which jumped to 80% for patients who had experienced at least some benefit from prior radiofrequency ablations.